استخدام كتاب العاجلة الفائدة لتعليم مهارة الكلام في مركز تبحر اللغة العربية بمعهد دار اللغة والكرامة - Mardiyah, Siti Faizah; Farid, Edi Kurniawan; Muzammil, Ahmad (MASALIQ, 2025)
This study aims to determine the effectiveness of using the book Al-'Ājilah al-Fā'idah in learning Arabic at the Arabic Language Development Institute (LPBA) Darul Lughoh wal Karomah (DWK). The book was chosen because it has a practical approach in mastering vocabulary and sentence structure that suits the needs of beginner students. The method used in this research is descriptive qualitative method with data collection techniques in the form of observation, interview, and documentation. The results showed that the use of Al-‘Ājilah al-Fā'idah was able to improve students’ understanding of Arabic language rules and accelerate the mastery of basic skills, especially in the aspects of reading and speaking. In addition, this book is also proven to be helpful in building the discipline of learning and motivation of students in studying Arabic. Thus, this book deserves to be used as one of the main references in the learning process of basic level Arabic in the pesantren environment.